Spirituality in clinical practice : theory and practice of spiritually oriented psychotherapy - Sperry, Len. (New York, NY : Routledge, 2012)
'While America is in the midst of a spiritual awakening, it is not surprising that psychotherapists are increasingly expected to incorporate the spiritual as well as the psychological dimension in their professional work. Therapists also are increasingly required to utilize evidence based practices and demonstrate the effectiveness of their practice. Unlike books that focus primarily on the therapist's spiritual awareness, the second edition of Spirituality in Clinical Practice addresses the actual practice of spiritually oriented psychotherapy from the beginning to end. Spirituality in Clinical Practice has been significantly updated and revised to emphasize the therapeutic processes in spiritually oriented psychotherapy with individual chapters on the therapeutic relationship, assessment and case conceptualization, intervention, termination and evaluation, as well culturally and spiritually sensitive interventions. As in the original edition, the second edition continues to provides a concise, theory-based framework for understanding the spiritual dimension. This framework then serves as the basis for competently integrating spirituality in effective, evidence-based psychotherapy practice. '--
'Spirituality in Clinical Practice is light years beyond books that emphasizes developing therapist awareness of spirituality; instead it emphasizes the effective integration of spirituality in all dimension of psychotherapy process: therapeutic alliance, assessment, case conceptualization, intervention, and termination'--
Includes bibliographical references and index.
Keywords: Psychotherapy -- Religious aspects; Counseling -- Religious aspects; Spirituality